4-Hydroxy-2-Nonenal Promotes Cardiomyocyte Necroptosis via Stabilizing Receptor-Interacting Serine/Threonine-Protein Kinase 1 - Zhai, Xiaoxuan; Wang, Wenjun; Sun, Shukun; Han, Yu; Li, Jiaxin; Cao, Shengchuan; Li, Ruochuan; Xu, Tonghui; Yuan, Qiuhuan; Wang, Jiali; Wei, Shujian; Chen, Yuguo (Frontiers in Cell and Developmental Biology, 2021)
Background: Necroptosis is a vital regulator of myocardial ischemia reperfusion (MI/R) injury. Meanwhile, 4-hydroxy-2-nonenal (4-HNE) is abundantly increased during MI/R injury. However, whether 4-HNE induces cardiomyocyte necroptosis during MI/R remains unknown. Methods: To observe the relationship between 4-HNE and necroptosis during MI/R, C57BL/6 mice and aldehyde dehydrogenase 2 transgenic (ALDH2-Tg) mice were both exposed to left anterior descending artery ligation surgery to establish MI/R injury models. For the further study, isolated mouse hearts and H9c2 cells were both treated with 4-HNE to elucidate the underlying mechanisms. Results: Necroptosis and 4-HNE were both upregulated in I/R injured hearts. Cardiomyocyte necroptosis was significantly decreased in I/R injured hearts from ALDH2-Tg mice as compared with that of wild mice. In vitro studies showed necroptosis was enhanced by 4-HNE perfusion in a time- and concentration-dependent manner. Knockdown of receptor-interacting serine/threonine-protein kinase 1 (RIP1) using siRNA prevented 4-HNE induced cardiomyocyte necroptosis, manifesting that RIP1 played a key role in the upregulation of cell necroptosis by 4-HNE. Further studies found that 4-HNE reduced the protein degradation of RIP1 by preventing K48-polyubiquitination of RIP1. Conclusions: 4-HNE contributes to cardiomyocyte necroptosis by regulating ubiquitin-mediated proteasome degradation of RIP1.